The quality of financial reporting in China: An examination from an accounting restatement perspective - Xia Wang; Min Wu (China Journal of Accounting Research, 2011)
This study uses restatements to reveal the poor quality of past accounting information reported within China's capital market. We show that up to a quarter of listed firms in mainland China explicitly admitted the poor quality of their financial information by restating their previous financial reports between 1999 and 2005. Many of these firms managed their earnings mainly via below-the-line items to avoid losses and promote survival, rather than to support refinancing goals. Such poor-quality financial reporting is more likely among firms that have weaker profitability and a shareholder base that is state-controlled, with diffused ownership and a relatively low proportion of shares held by institutional investors. Furthermore, we find the market to be relatively insensitive to such admissions. Investors' reactions capture only the earnings information of the current reported year, rather than also reflecting the concurrently revealed correction of past financial reporting. However, the equity market does not completely ignore the earnings information. Investors' reliance on earnings is merely low relative to the mature US market. These findings demonstrate that accounting credibility in China has low value; providing poor-quality financial information bears little cost because various market mechanisms fail to deter such behavior. Nevertheless, regulators' ongoing efforts to enhance the quality of financial information and disclosure among listed firms are still fruitful. The frequency of restatements decreased over our sample period, which reinforces the current regulatory prospects and strategies for further improving China's capital markets.
Keywords: M41; 650; Earnings quality; Earnings management; Restatements; China capital markets; Regulation; Disclosure